Current advances of Pichia pastoris as cell factories for production of recombinant proteins - Pan, Yingjie; Yang, Jiao; Wu, Jianping; Yang, Lirong; Fang, Hao (Frontiers in Microbiology, 2022)
Pichia pastoris (syn.Komagataella spp.) has attracted extensive attention as an efficient platform for recombinant protein (RP) production. For obtaining a higher protein titer, many researchers have put lots of effort into different areas and made some progress. Here, we summarized the most recent advances of the last five years to get a better understanding of its future direction of development. The appearance of innovative genetic tools and methodologies like the CRISPR/Cas 9 gene-editing system eases the manipulation of gene expression systems and greatly improves the efficiency of exploring gene functions. The integration of novel pathways in microorganisms has raised more ideas of metabolic engineering for enhancing RP production. In addition, some new opportunities for the manufacture of proteins have been created by the application of novel mathematical models to have a better overview of bottlenecks in the biosynthetic process.